A compact UWB antenna with dual 3.5/5.5 GHz band‐notched characteristics. Issue 3 (March 2015) - Tripathi, Shrivishal; Mohan, Akhilesh; Yadav, Sandeep
ABSTRACT In this article, a compact octagonal‐shaped UWB antenna with Minkowski fractal‐shaped notch and a dual C‐shaped notch is presented. The Minkowski fractal helps to obtain band rejection at WiMAX (3.4–3.7 GHz) band, whereas dual C‐shaped notch on either side of feed line provides the band rejection at WLAN (5.15–5.825 GHz) band. Moreover, a rectangular slot is also inserted in the ground plane, which helps to obtain the desired UWB bandwidth. The proposed antenna has the compact size of 26 × 16.5 mm2. The proposed antenna shows proper impedance matching, stable radiation pattern with good antenna gain (2–5 dBi) over the entire UWB frequency range. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:551–556, 2015